2020
DOI: 10.1016/j.beem.2019.101365
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, diagnosis and outcomes of treatment for primary aldosteronism

Abstract: Primary aldosteronism (PA) is the most common potentially curable form of hypertension. The overproduction of aldosterone leads to an increased risk of cardiovascular and cerebrovascular events as well as adverse effects to the heart and kidney and psychological disorders. PA is mainly caused by unilateral aldosterone excess due to an aldosterone-producing adenoma or bilateral excess due to bilateral adrenocortical hyperplasia. The diagnostic work-up of PA comprises three steps: screening, confirmatory testing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 136 publications
1
30
0
3
Order By: Relevance
“…Chronic inappropriate elevations in aldosterone can increase pro-inflammatory cytokines [4] and cause oxidative stress [5], which in the long-term leads to tissue damage and fibrosis [6]. As a result PA patients have higher cardiovascular risk than those with essential hypertension suggesting an impact of inappropriate aldosterone that is beyond increased blood pressure [7][8][9]. Moreover, the increased risk of morbidity at least with regard to cardiac remodeling may be reversible through targeted management with surgery or medical treatment that includes the use of mineralocorticoid receptor antagonist [8,10].…”
Section: Overview Of Primary Aldosteronism (Pa)mentioning
confidence: 99%
“…Chronic inappropriate elevations in aldosterone can increase pro-inflammatory cytokines [4] and cause oxidative stress [5], which in the long-term leads to tissue damage and fibrosis [6]. As a result PA patients have higher cardiovascular risk than those with essential hypertension suggesting an impact of inappropriate aldosterone that is beyond increased blood pressure [7][8][9]. Moreover, the increased risk of morbidity at least with regard to cardiac remodeling may be reversible through targeted management with surgery or medical treatment that includes the use of mineralocorticoid receptor antagonist [8,10].…”
Section: Overview Of Primary Aldosteronism (Pa)mentioning
confidence: 99%
“…The median age and BMI were 43 years (18-73) and 27 kg/m 2 (20-46), respectively. The median duration of HTN was 2.3 years (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Median preoperative systolic and diastolic BP was 150 mmHg (110-249) and 98 mmHg (70-151) on 3 (1-8) antihypertensives.…”
Section: Resultsmentioning
confidence: 99%
“…Primary aldosteronism (PA) is present in up to 33% of patients with secondary hypertension (HTN) [1]. It is characterized by renin-independent excess aldosterone which leads to drug-resistant hypertension and hypokalemia [2]. The source of aldosterone excess in PA may be from one adrenal gland as a result of an aldosterone-producing adenoma (APA) or unilateral hyperplasia.…”
Section: Introductionmentioning
confidence: 99%
“…Studies that evaluated the prevalence of PA based on hypertension grades showed a prevalence of 2.0% to 6.6% in grade I hypertension, 8.0% to 15.5% in grade II hypertension, and 11.8% to 19% in grade III hypertension. [22][23][24] Moreover, it increased to 20% in patients with resistant hypertension. 25 In the present study, the prevalence of PA was 3.31% in participants with general hypertension; however, as found in previous studies, the prevalence significantly increased with the hypertension grading (0.68%, 3.38%, and 12.64% among patients with grade I, II, and III hypertension, respectively).…”
Section: Discussionmentioning
confidence: 99%